Effectiveness of the dento activity book on preschool children's dental health knowledge : experimental study - Kurniawati, Dwi; Lupianto, Della Kusumawati; Sari, Morita; Kaswindiarti, Septriyani (Padjadjaran Journal of Dentistry, 2026)
Introduction: Poor dental health in early childhood is a significant concern. Data from Basic Health Research (Riskesdas) indicate an alarming increase in the percentage of the Indonesian population experiencing dental and oral problems, rising from 25.9% in 2013 to 57.6% in 2018. A major contributing factor to the prevalence of these issues is a lack of knowledge. Education is essential for enhancing awareness and understanding. This study aims to evaluate the effectiveness of the Dento Activity Book in improving preschool children's knowledge about maintaining dental and oral health.Methods: This research utilizes a quasi-experimental design that features a pre-post test with a non-equivalent control group. A total of 46 children from Permata Hati Islamic Kindergarten/KB were selected as participants. Knowledge was assessed through a questionnaire administered before and after the educational intervention. The data were analyzed using the Mann-Whitney U test.Results: The average knowledge score for the treatment group increased by 1.96, while the control group saw an increase of 0.30, yielding a significant value of 0.00 (p < 0.05).Conclusion: The Dento Activity Book effectively enhances preschool children's understanding of how to maintain their dental and oral health.